Development of motivation and functional preparation for competitions at the rugby players in the Children's Sports School - Muminov M; Muminov X.M (Zien Journals, 2023)
The article discusses issues on the development of rugby in Uzbekistan, the presidential decree on the development of rugby in our country, rugby as a symbiosis of athletics and freestyle wrestling, motivation among rugby players in the Sports and Youth Sports School and their physical, moral, mental and tactical training. Running as a vital element for rugby players. Ball throwing. Motivate rugby players because rugby is a team game, so every detail of each player is important here, taking into account the understanding of rugby players among themselves during training and in competitions Motivation as a complex solution to the problems of team sports
Keywords: Sports training; Motivation; Running; throwing